Anterior Ankle Skin Surface Pressures in Lower Extremity Splints: Minimizing Insult after Injury. Issue 1 (January 2022) - Walton, David M.; Farrar, Nicholas; Shams, Kameron A.; Mell, Kristopher; Holmes, James R.; Talusan, Paul G.
Category: Ankle; Trauma; Other Introduction/Purpose: Though ubiquitously utilized in orthopaedic trauma, lower extremity splints are not without their associated iatrogenic risk of morbidity. In fact, improper splinting not only necessitates replacement, but splint-related soft tissue complications are the second most common iatrogenic cause for referral to plastic surgery. Improper splinting techniques include inadequate molding of plaster/fiberglass splints, inadequate padding over bony prominences, excessive compressive forces from elastic bandages applied too aggressively, and/or pressure areas created by applying padding and casting material in varying joint positions. While clinicians commonly pad bony prominences to minimize skin pressure, the effect of joint position on skin pressure and, more specifically, changing joint position, is understudied. The purpose of this study is to evaluate anterior ankle skin pressure secondary to joint position change during splinting. Methods: Following ethics approval by our institutional review board, various constructs of lower extremity, short-leg splints were applied to two healthy subjects (2 limbs total in this preliminary data set) with an underlying pressure transducer (Tekscan I- Scan system (Tekscan Inc, South Boston, MA, USA) on the skin surface centered on the anterior ankle on the tibialis anterior tendon. All subjects underwent anterior ankle surface pressure assessment when padding was applied in maximum plantar flexion and neutral position for conventional short leg splints application. Percent change from initial contact pressure centered on the tibialis anterior with either Webril (Covidien/Medtronic, Dublin, Ireland), or Specialist Cotton Blend Cast Padding (BSN Medical, Charlotte, NC, USA) were calculated. Neutral position of the foot/ankle will be confirmed with goniometer. Results: There were 2 limbs total that were analyzed for the presentation of pilot data for this study. The percent change in anterior ankle contact pressure when padding was applied in maximum plantarflexion (PF) and then placed in neutral was increased at least two-fold without the addition of plaster and subsequently with the addition of plaster in lower extremity short leg splints (Figure 1). Conclusion: In this pilot data, we report significant increases in anterior ankle contact pressures when splint padding is applied in plantar-flexion and re-positioned into neutral during splint application which may precipitate iatrogenic pressure ulcers in patients sustaining foot/ankle trauma. This data, though preliminary, underscores the importance in proper splinting techniques for all clinicians that manage lower extremity trauma (eg, orthopaedic surgery, emergency medicine, urgent care, etc).